Integrating Indigenous Knowledge “Sedekah Ramo” into Elementary Social Studies: A Culturally Responsive Teaching Approach - Felly Valiana; Kirana Prama Dewi (International Journal of Learning Reformation in Elementary Education, 2026)
Indigenous knowledge, known as "sedekah ramo," refers to the local knowledge of the Bulang Tengah Suku Ulu community in Musi Rawas, South Sumatra. "Sedekah ramo" is closely related to various concepts in social studies learning. The integration of local wisdom into social studies education is important for creating contextual and meaningful learning. However, studies on its application through the CRT approach in elementary schools remain limited. This study aims to describe the integration of IK "sedekah ramo" as a source of IPS learning through the CRT approach for fifth-grade students at SD Negeri 1 Bangun Jaya. The research used a qualitative descriptive case study design, with data collected through observation, interviews, and documentation. The primary participants consisted of one fifth-grade social studies teacher and twenty-five fifth-grade students. Data analysis was systematically conducted using the interactive model developed by Miles, Huberman, and Saldaña, which encompasses data condensation (reduction), data display, and conclusion drawing. The research results show that integration is carried out through lesson planning, the implementation of CRT-based learning that builds an inclusive and participatory environment, the evaluation of cognitive, affective, and psychomotor aspects, and the assessment of the success of integrating local knowledge into social studies learning. This research is expected to serve as an alternative to social studies learning grounded in local culture through the CRT approach and to enrich social studies instruction grounded in indigenous knowledge in multicultural elementary schools with limited learning facilities.